Love, Learn, Protect: Assessing the short-term impact of Lisbon Zoo school education programs on 10-18 years old students - Rato, Daniela Cristina Pataquinho (2021)
Tese de mestrado, Biologia da Conservação, Universidade de Lisboa, Faculdade de Ciências, 2020